Relación entre el crecimiento del crédito directo y el nivel de inflación en Loreto, periodo 2015 - 2020 - Navarro Guerra, Ney Javier (2022)
The department of Loreto is the one with the largest geographical area compared to the other departments of the Peruvian territory, for this reason it is of great importance to have a clear and fundamental technical knowledge about the main macroeconomic variables that make up the economic system of the region. Given this premise, the initiative of this research was born, since it will seek to determine what type of relationship one of the determining factors that the financial system has at its disposal, the authorities such as the Superintendence of Banking, Insurance and AFP (SBS) and the Central Reserve Bank of Peru (BCRP), which refers to direct credit, with the inflation rate (both variables corresponding to the Loreto region) during the period of time 2015 - 2020, and verify if said relationship is significant or No. The results show that there is a positive relationship between the study variables since a value of the Pearson consequence coefficient is obtained in relative terms of 42.52 percent. In another instance, it is determined through the estimation of a linear regression econometric model that the relationship between the inflation rate and the growth of direct credit is significant since a p-value corresponding to the estimator of the coefficient of the independent variable was obtained (direct credit growth) of 0.00019, which is less than 0.05, taking into account that the level of significance used was 5 percent.